1984
DOI: 10.1056/nejm198410043111401
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Hearing Impairment as a Sequela of Acute Bacterial Meningitis

Abstract: As part of a prospective study of acute bacterial meningitis in children, we studied for five years the hearing of 185 infants and children who had acute bacterial meningitis when they were more than one month of age. Nineteen (10.3 per cent) of the patients had persistent bilateral or unilateral sensorineural hearing loss. The incidence of hearing loss as determined by electric-response audiometry and conventional tests was 31 per cent with Streptococcus pneumoniae, 10.5 per cent with Neisseria meningitidis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
160
1
12

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(193 citation statements)
references
References 26 publications
20
160
1
12
Order By: Relevance
“…Vários autores destacam a meningite bacteriana como uma das principais causas de surdez adquirida após o nascimento 7 . Do ponto de vista fisiopatológico, a perda auditiva na meningite bacteriana provavelmente ocorre no início da doença, durante a fase de bacteremia, antes que se evidenciem os sinais e sintomas clínicos.…”
Section: Discussionunclassified
“…Vários autores destacam a meningite bacteriana como uma das principais causas de surdez adquirida após o nascimento 7 . Do ponto de vista fisiopatológico, a perda auditiva na meningite bacteriana provavelmente ocorre no início da doença, durante a fase de bacteremia, antes que se evidenciem os sinais e sintomas clínicos.…”
Section: Discussionunclassified
“…The most common neurological complication in children is some degree of sensorineural hearing impairment. A prospective study of acute bacterial meningitis in children showed that "'-' I0% of patients had persistent bilateral or unilateral sensorineural hearing loss [17]. This impairment is most likely secondary to cochlear dysfunction due to the presence of viable bacteria in the cochlea and cochlear aqueduct.…”
Section: Morphological Alterations During Bacterial Meningitismentioning
confidence: 99%
“…For example, microbial infections of the middle ear, such as with Streptococcus pneumoniae (Dodge et al ., 1984), Haemophilus influenzae type B (Feldman et al ., 1982), or cytomegalovirus (Bradford et al . 2015), can spread to the inner ear and induce inflammation resulting in sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%